The Ground at My Feet : Sustaining a Family and a Forest - Stinson, Ann (Book collections on Project MUSE., 2021)
"Ann Stinson grew up on her family's tree farm in southwestern Washington state, on a ridge above the Cowlitz River. After building a life in New York and Portland, she returned home at the age of fifty, when her brother's death from cancer left her manager and co-owner of three hundred acres planted in Douglas fir, western red cedar, and ponderosa pine. The Ground at My Feet is a memoir about loss and grief as well as a portrait of a family, a region, and an industry. Combining personal story and research, Stinson weaves essays, poems, history, and science into a rich and layered account of life in a family forest in the Pacific Northwest. She maps interactions between the land and its people over two centuries: the Cowlitz peoples, homesteaders, and several generations of logging families who have worked the property. She follows her family's logs as they become lumber for fence boards and suburban homes, touring a local cedar mill and traveling with her father to visit mills in Japan. Stinson adds a landowner's voice to conversations about the human tendency to demand more of the land than it can sustain. With its uniquely personal view of the Pacific Northwest's timber and forestry heritage, The Ground at My Feet is an engaging addition to the literature of the landscape and ecology of the West"--